Determinant Factors Affecting Fraud Detection Capabilities to The External Auditor in Jakarta - Triana Yuniati; Erliana Banjarnahor (Universitas Trisakti, 2019)
The perspective of this study provides empirical evidence on the factors that affect the auditor's fraud detection ability. There are effective research hypotheses with auditor tenure, fraud detection experience, level of education, fraud training, prof professional skepticism. This study is hypothesis-testing research, Respondents are 120 auditors from seven public accounting firms in Jakarta participated in this study, thought a questionnaire. Data collected is done during April 201 5 by visiting the public accounting firm that has been willing to participate in this study. The type of data used is primary data and is a cross-section, data is collected only once. Conclusion of the study is auditor tenure, fraud training does not affect the ability to detect fraud. While fraud detection experience, the auditor's level of education and professional skepticism positively influence fraud detection capability. Limitations, suggestions and research implications are described at the end of this report.